2021
DOI: 10.3389/fnhum.2021.742198
|View full text |Cite
|
Sign up to set email alerts
|

Acute White Matter Integrity Post-trauma and Prospective Posttraumatic Stress Disorder Symptoms

Abstract: Background: Little is known about what distinguishes those who are resilient after trauma from those at risk for developing posttraumatic stress disorder (PTSD). Previous work indicates white matter integrity may be a useful biomarker in predicting PTSD. Research has shown changes in the integrity of three white matter tracts—the cingulum bundle, corpus callosum (CC), and uncinate fasciculus (UNC)—in the aftermath of trauma relate to PTSD symptoms. However, few have examined the predictive utility of white mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Of note, we did not observe effects in canonical threat circuitry often associated with PTSD. Past studies have not typically considered childhood maltreatment when evaluating white matter markers of PTSD susceptibility [15][16][17][18], and it is possible that reduced IC FA may be a sequela of childhood maltreatment exposure. Moreover, although we analyzed imaging data from over 200 participants, we could have been underpowered to detect all effects with our unbiased whole-brain analytic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, we did not observe effects in canonical threat circuitry often associated with PTSD. Past studies have not typically considered childhood maltreatment when evaluating white matter markers of PTSD susceptibility [15][16][17][18], and it is possible that reduced IC FA may be a sequela of childhood maltreatment exposure. Moreover, although we analyzed imaging data from over 200 participants, we could have been underpowered to detect all effects with our unbiased whole-brain analytic approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, PTSD was associated with reductions in CGC integrity, whereas neighborhood disadvantage was not. Prior work has suggested that lesser integrity of the CGC was associated with greater psychophysiological responses to threatening cues and lesser integrity is prospectively associated with future PTSD symptoms . Future directions may include evaluating the association between structure and function in populations with chronic PTSD symptoms to investigate whether this outcome is timing specific.…”
Section: Discussionmentioning
confidence: 99%
“…The second sample was derived from another large longitudinal study, independent from Sample A, that was designed to identify acute posttrauma risk factors for PTSD development in adults using biospecimen, self‐report measures, cognitive and behavioral assessments, and neuroimaging (i.e., Bird et al., 2021; Webb, Weis, Huggins, Fitzgerald, et al., 2021; Webb, Weis, Huggins, Parisi, et al., 2021; Weis et al., 2021, 2022). Enrolled participants were recruited after being discharged from the ED after a single‐incident traumatic injury (86.0% nonassaultive, 14.0% assaultive trauma) and completed seven study visits.…”
Section: Methodsmentioning
confidence: 99%